Pricing Strategies in E-Commerce: Bricks vs. Clicks - Richard Friberg; Mattias Ganslandt; Mikael Sandström (The Research Institute of Industrial Economics (IUI), 2001)
What is the impact of the increasing dominance of conventional firms in e-commerce? We use a simple model to show that retailers who only sell through Internet have lower on-line prices than retailers who also sell through conventional stores. This proposition is firmly supported by our empirical analysis which uses a rich data set covering the Swedish markets for books and CDs. On average, prices of these goods are 15 percent cheaper on Internet, but if a single item is bought transport costs will make it as expensive to buy over Internet as in a conventional store (if a basket of goods is bought it is some 10 percent cheaper on Internet since transport costs are fixed).
Keywords: D12; D43; L11; L81; 330; Retail Pricing; Consumer Behavior; E-Commerce; Price Discrimination; E-Business; Preismanagement; Bespielte Medien; Buchhandel; Schweden